The Effect of Index Card Match Method to The Math Critically Thinking Skill Oriented to Higher Order Thinking Skills (HOTS) - Firda Halawati Bayasut (Indonesian Journal of Mathematics Education, 2019)
This study aims to: (1) find out the use of the Index Card Match method in mathematics; (2) determine the students’ ability of mathematics critical thinking with Higher Order Thinking Skills (HOTS); (3) determine whether there is an influence of the use of Index Card Match method to the students’ ability of mathematics critical thinking with HOTS. This study uses the pre-experimental method with one group for the pretest-posttest design. The population in this study was all students of Senior High School in Kadugede, Kuningan, West Java, totaling 1008 students. The sampling technique used was purposive sampling. The sample of this study was taken from two classes from class VII D as a control class with 37 students and class VII E as an experimental class with 38 students. The test instruments used were multiple-choice questions. Tests were given at the initial test (pretest) and final test (posttest). The testing data were analyzed using the independent samples t-test which has previously been tested for normality and homogeneity. The results of this study indicate: (1) the use of the Index Card Match method in mathematics learning in the experimental class was positively well and students looked serious and enthusiastic in following the teaching and learning process; (2) The students’ ability of mathematics critical thinking by using the Index Card Match method increased both in the experimental and control classes; (3) There was an influence of the use of the Index Card Match method in students' ability of mathematics critical thinking oriented to HOTS.